INNOVATIVE APPROACHES IN DIGITAL ATTENDANCE SYSTEMS: EVALUATING THE EFFECTIVENESS OF QR CODE, FACE RECOGNITION, AND GPS METHODS - Nur Kholis, Frengki; Maliya, Azka; Muawanah, Kholisotul; Rosit, Fathor; Suparto, Arico Ayani (Journal on Research and Review of Educational Innovation, 2024)
Digital attendance is a soft device or application computer designed​ to monitor and record somebody's presence systematically. Application This replaces the traditional manual way of recording and tracking the presence of employees, students, and others using digital technology. Applications for digital attendance usually implement various feature technologies such as QR Code, fingerprint finger, introduction face, RFID ( Radio Frequency Identification ), or GPS ( Global Positioning System ) to entertain accuracy and security recording presence. The study aims to obtain information about the practical method development application of existing digital attendance. Research This uses the method of systematic literature review (SLR). Stage identify, study, evaluate, and interpret all the existing research results. This study finds three effective ways​ To develop application digital attendance: QR code, fingerprint finger, and RFID. In addition, there are fewer​ effective ways to build an application with digital time and presence, such as introducing face and GPS. Methods This vulnerable error needs investigation To get a percentage of high database results. Lack of availability time is influenced by factors deep data research determines results database system is inhibiting development application logger time and digital presence. Therefore, a step further in application absence is to apply a method proven to be​ effective so that the stage development application study is fluent.